Sustainable Development Goals (SDGs) and Regulatory Reform: A Legal Approach to Responsive and Sustainable Lawmaking (International Forum of Researchers and Lecturers, 2025)
This study examines the critical need for regulatory reform in Indonesia to effectively incorporate the principles of the Sustainable Development Goals (SDGs) into the national legislative framework. Employing a normative juridical method, the research highlights a fundamental disconnect between Indonesia’s long-term and medium-term development planning documents (RPJPN and RPJMN) and the National Legislation Program (Prolegnas). This disconnection results in fragmented and sectoral regulations that hinder progress toward achieving SDG targets. The findings reveal that the current legal landscape in Indonesia is predominantly reactive, lacks coherence across sectors, and is not oriented toward sustainability. Contributing to this issue is the absence of SDG-based regulatory impact assessments and the minimal involvement of the public in the legislative process. These shortcomings not only weaken the regulatory system but also reduce the effectiveness of laws in supporting inclusive and sustainable development. To address these gaps, the study proposes several strategic reforms. These include integrating an SDGs checklist into the preparation of academic legislative drafts, enhancing institutional capacities for sustainability governance, and adopting international best practices from countries that have successfully embedded SDG principles into their legal structures. Furthermore, the study emphasizes the importance of repositioning the SDGs as a guiding framework in the national lawmaking process. By doing so, Indonesia can create regulations that are not only responsive to current societal needs but also aligned with long-term sustainability goals. Overall, this research underscores the necessity of transforming Indonesia’s legal development paradigm to produce laws that are coherent, inclusive, and future-oriented in support of the 2030 Agenda for Sustainable Development.